Long working hours and depressive symptoms: systematic review and meta-analysis of published studies and unpublished individual participant data - Marianna Virtanen; Markus Jokela; Ida EH Madsen; Linda L Magnusson Hanson; Tea Lallukka; Solja T Nyberg; Lars Alfredsson; G David Batty; Jakob Bue Bjorner; Marianne Borritz; Hermann Burr; Nico Dragano; et al. (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVES: This systematic review and meta-analysis combined published study-level data and unpublished individual-participant data with the aim of quantifying the relation between long working hours and the onset of depressive symptoms. METHODS: We searched PubMed and Embase for published prospective cohort studies and included available cohorts with unpublished individual-participant data. We used a random-effects meta-analysis to calculate summary estimates across studies. RESULTS: We identified ten published cohort studies and included unpublished individual-participant data from 18 studies. In the majority of cohorts, long working hours was defined as working ≥55 hours per week. In multivariable-adjusted meta-analyses of 189 729 participants from 35 countries [96 275 men, 93 454 women, follow-up ranging from 1-5 years, 21 747 new-onset cases), there was an overall association of 1.14 (95% confidence interval (CI) 1.03-1.25] between long working hours and the onset of depressive symptoms, with significant evidence of heterogeneity (I^2=45.1%, P=0.004). A moderate association between working hours and depressive symptoms was found in Asian countries (1.50, 95% CI 1.13-2.01), a weaker association in Europe (1.11, 95% CI 1.00-1.22), and no association in North America (0.97, 95% CI 0.70-1.34) or Australia (0.95, 95% CI 0.70-1.29). Differences by other characteristics were small. CONCLUSIONS: This observational evidence suggests a moderate association between long working hours and onset of depressive symptoms in Asia and a small association in Europe.